Βιβλιογραφικό σημείωμα: Michiel D. J. Op de Coul† (ed.), Theodori Prodromi Epistulae et Orationes [CCSG 81], Turnhout 2023 - ΛΑΜΠΑΚΗΣ, Στυλιανός (Byzantina Symmeikta, 2024)
Βιβλιογραφικό σημείωμα: Michiel D. J. Op de Coul† (ed.), Theodori Prodromi Epistulae et Orationes [CCSG 81], Turnhout 2023